2017
DOI: 10.7322/jhgd.137515
|View full text |Cite
|
Sign up to set email alerts
|

Contributions in the field of Public Health for decision-making in health

Abstract: Brazil has made a wide development and contribution in the field of Public Health. These contributions have maximized public health decision-making, which is a factor of great importance for the maintenance of health of a given population, either in the prevention of disease, as is the case of immunizations or with actions in Health Promotion, improving the quality of life of the affected population. Thus, the Journal of Human Growth and Development has contributed enormously to the dissemination of knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(20 reference statements)
0
2
1
Order By: Relevance
“…However, our findings disagree with those of Miranzi et al 29 , who, when studying 30 individuals with hypertension and diabetes, and who were attended by a Family Health Team (FHT) in the state of Minas Gerais, Brazil, found that the Environment domain had high scores, being among those who collaborated most with the positive evaluation of QoL. In fact, the surrounding environment has been recurrently presented as a key factor for people's health and QoL [30][31][32][33] .…”
Section: Discussioncontrasting
confidence: 96%
“…However, our findings disagree with those of Miranzi et al 29 , who, when studying 30 individuals with hypertension and diabetes, and who were attended by a Family Health Team (FHT) in the state of Minas Gerais, Brazil, found that the Environment domain had high scores, being among those who collaborated most with the positive evaluation of QoL. In fact, the surrounding environment has been recurrently presented as a key factor for people's health and QoL [30][31][32][33] .…”
Section: Discussioncontrasting
confidence: 96%
“…We have the COVID-19 pandemic as a global problem 22 and it has consequences for the population in a way where non-pharmacological measures, such as isolation, interfere with the population's quality of life and for that reason, there is the need for greater discussion so that public policies focused on health promotion can contribute to better longevity 23 . It is still perceived the need to provide means to help broaden the discussion of the topic with a focus on the production of knowledge in search of at least broadening the discussions with the objective that the health area seeks to work with better prevention 24 .…”
Section: Discussionmentioning
confidence: 99%
“…It also emphazised the importance of research that can contribute to new paths in obtaining public health in a given community, as well as knowledge transfer. [ 54 ]…”
Section: Discussionmentioning
confidence: 99%